2010
DOI: 10.1002/jcb.22766
|View full text |Cite
|
Sign up to set email alerts
|

The odontogenic ameloblast‐associated protein (ODAM) cooperates with RUNX2 and modulates enamel mineralization via regulation of MMP‐20

Abstract: We have previously reported that the odontogenic ameloblast-associated protein (ODAM) plays important roles in enamel mineralization through the regulation of matrix metalloproteinase-20 (MMP-20). However, the precise function of ODAM in MMP-20 regulation remains largely unknown. The aim of the present study was to uncover the molecular mechanisms responsible for MMP-20 regulation. The subcellular localization of ODAM varies in a stage-specific fashion during ameloblast differentiation. During the secretory st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 44 publications
3
56
0
1
Order By: Relevance
“…Odam and Mmp-20, ameloblast differentiation markers, were expressed during ameloblast differentiation ( Fig. 1(A and B)), as expected [12]. Furthermore, secretory Cpne7 was clearly detected in ameloblast conditioned medium (CM) from day 4 (preameloblast stage) and then decreased thereafter ( Fig.…”
Section: Preameloblasts Secrete Cpne7 During Ameloblast Differentiationsupporting
confidence: 75%
See 1 more Smart Citation
“…Odam and Mmp-20, ameloblast differentiation markers, were expressed during ameloblast differentiation ( Fig. 1(A and B)), as expected [12]. Furthermore, secretory Cpne7 was clearly detected in ameloblast conditioned medium (CM) from day 4 (preameloblast stage) and then decreased thereafter ( Fig.…”
Section: Preameloblasts Secrete Cpne7 During Ameloblast Differentiationsupporting
confidence: 75%
“…Briefly, proteins (30 mg) were separated by 10% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and transferred to nitrocellulose membranes. Rabbit and affinity-purified polyclonal anti-Odam, anti-Cpne7, and anti-Dsp antibodies were produced as described previously [6,12]. The Flag (F3165) antibody was purchased from SigmaeAldrich (St. Louis, MO).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…En el 2010, Lee y colaboradores 22 estudiaron los mecanismos moleculares responsables de la regulación de la MMP-20, encontrando que la fase secretora de la amelogénesis ODAM (proteína asociada a ameloblastos odontogénicos) se localizó en el núcleo y citoplasma de los ameloblastos, y la etapa de maduración se observó en el citoplasma y en la interfaz entre los ameloblastos y la capa de esmalte, pero no en el núcleo. Se sugiere que Runx2 regula la expresión de ODAM nuclear que tiene una función reguladora importante en la mineralización del esmalte a través de la regulación de la MMP-20.…”
Section: Cultivos Celularesunclassified
“…In 2010, Lee et al, 22 studied the molecular mechanisms responsible for the regulation of MMP-20, finding out that the secretory phase of amelogenesis ODAM (odontogenic-ameloblast-associated protein) was located in the nucleus and cytoplasm of ameloblasts, and maturation stage was observed in the cytoplasm and at the interface between the ameloblasts and enamel coating, but not in the nucleus. It is suggested that Runx2 regulates the expression of nuclear ODAM playing an important regulatory role in the mineralization of enamel through regulation of MMP-20.…”
Section: Cell Culturesmentioning
confidence: 99%
“…During tooth development, this protein is involved in matrix protein production (Lee et al, 2012b). In ameloblasts, nuclear Odam has been reported as a regulator of the expression of matrix metalloproteinase-20 (MMP-20), a gene that is responsible for the mineralization of enamel (Lee et al, 2010a). Also, Odam is expressed in malignant ameloblasts and other types of human neoplastic cells, including those of gastric, lung, and breast origins but the precise function of Odam in these cancers is not known (Kestler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%